Sustainability of Education for Children of Underprivileged Families through the Family Hope Program (PKH) - Dairizki Dairizki (Ruhama : Islamic Education Journal, 2022)
The sustainability of generational education is the responsibility of all parties, in the law it is affirmed that every citizen has the right to get a decent education. Therefore, the government of the Republic of Indonesia has set various policies to help the success of the compulsory education program, among the established programs is the Family Hope Program (PKH). In reality, the existence of this program has not been in accordance with the targets and targets expected by the government. Related to the problems described above, this study aims to reveal how the impact of the family hope program on improving education. The research was conducted with a qualitative approach, data were collected with interview techniques, observations and documentation studies. The results of the study are first, KPM Insights into the Family Hope Program, both Underprivileged families have understood and knew, the goals and rules contained in the Family Hope Program. Second, PKH's position to support the learning of students who come from underprivileged families is the provision of cash and non-cash assistance to PKH participants to meet the needs and administrative equipment in schools. Third, the assistance provided by PKH in supporting the learning of students who come from poor families with positive results is to ease the burden of expenditure for beneficiary families (KPM).